Optimization of Window Size for Calculating Semantic Coherence Within an Essay - Srivastava, Kshitiz; Dhanda, Namrata; Shrivastava, Anurag (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2022)
Over the last fifty years, as the field of automated essay evaluation has progressed, several ways have been offered. The three aspects of style, substance, and semantics are the primary focus of automated essay evaluation. The style and content attributes have received the most attention, while the semantics attribute has received less attention. A smaller fraction of the essay (window) is chosen to measure semantics, and the essay is broken into smaller portions using this window. The goal of this work is to determine an acceptable window size for measuring semantic coherence between different parts of the essay with more precision.